The PROSPER Toolkit - Dennis, Louise Abigail; Collins, Graham; Norrish, Michael; Boulton, Richard; Slind, Konrad; Robinson, Graham; Gordon, Mike; Melham, Tom (Springer, 2000)
The PROSPER (Proof and Specification Assisted Design Environments) project advocates the use of toolkits which allow existing verification tools to be adapted to a more flexible format so that they may be treated as components. A system incorporating such tools becomes another component that can be embedded in an application.